2021
DOI: 10.3390/agronomy11010125
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Possibilities of Using Cross-Linked Polyacrylamide (Agro Hydrogel) and Preparations with Biostimulation in Building the Quality Potential of Newly Planted Apple Trees

Abstract: The research was carried out in a commercial apple orchard in southeastern Poland. The aim of the research was to evaluate the effect of fertilizer with biostimulation and humic acids with algae extracts and agrogel on the reception and growth of newly planted maiden apple trees of the ‘Gala Must’ variety. One-year-old budwoods were planted annually on the site where fruit trees had grown for 20 years. For the purpose of the experiment, old trees were grubbed up every year in autumn. The experiment assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Hydrogel application was in coincidence with the cell expansion stage, which continued for a longer period compared to the control. The present result is confirmed by the previous work of Kaplan [ 23 ], who found that the application of hydrogel at a moderate concentration gave maximum growth parameters using a level of 500 g∙plant −1 apple ‘Gala Must’ variety. These results concur with those of Awad et al [ 24 ] in the apple seedling and those of Cavalcante et al [ 25 ] in passion fruit.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Hydrogel application was in coincidence with the cell expansion stage, which continued for a longer period compared to the control. The present result is confirmed by the previous work of Kaplan [ 23 ], who found that the application of hydrogel at a moderate concentration gave maximum growth parameters using a level of 500 g∙plant −1 apple ‘Gala Must’ variety. These results concur with those of Awad et al [ 24 ] in the apple seedling and those of Cavalcante et al [ 25 ] in passion fruit.…”
Section: Resultssupporting
confidence: 91%
“…This result is related to the improvement of soil water and nutrient absorption by adding hydrogel. The nutrients taken by hydrogels from the soil are released by plants through an exchange relationship when they need nutrients for growth [ 1 , 23 ]. This action leads to improving the growth-boosting effect of hydrogel application.…”
Section: Resultsmentioning
confidence: 99%
“…As reported by DeBoer [19], polyphenols in plants not only have a health-promoting effect on the human body but also perform important defined functions in plant organisms. Many authors have reported that the use of programs based on seaweed extracts increases the biological performance of plants, has an anti-stress effect on plants, and strengthens the defined functions of plant organisms [28,45,46]. In a research paper by Sylvia et al [47], the authors evaluated the effects of seaweed extracts on the antioxidant activity and polyphenol content of fruit, and found a program containing a combination of several biostimulants to be the most effective.…”
Section: Discussionmentioning
confidence: 99%
“…For example, see the reviews on the techniques of hydrogel polymerization (synthesis parameters, various cross-linking methods), [2] hydrogel microarchitecture (solvent casting/particle leaching, freeze-drying, gas foaming, or electrospinning), [3] and hydrogel nanofibers (synthesis, properties, and applications). [4] Polyacrylamide (PAAm) hydrogels can be used in many different areas ranging from oil recovery, [5][6][7] over medicine or landscape cultivation, [8][9][10][11] to waste water treatment. [12][13][14] Although acrylamide monomer (AAm) is neurotoxic, the PAAm polymer is non-toxic [15,16] and PAAm hydrogels are therefore widely used especially in medicine.…”
Section: Introductionmentioning
confidence: 99%